UPAYA PENURUNAN PRODUK CACAT DEPARTEMEN BLOW MOLDING PT. X SURABAYA - Julius Chang; Tanti Octavia (Jurnal Titra, 2017)
Quality is a very important thing to be considered in every company because it relates to customer satisfaction. However, defective products often occur in the production activities, the management attempts to decrease defective products since it causes the loss in time, material, and funds used. Measurement System Analyze is applied as the first stage to perform an analysis toward the ability of the operator, technicians, and QC inspector. The next stage is to make Fishbone Diagram to find out the roots problems of defective products on Blow Molding area. The Measurement System Analyze results shows that 61.7% of the entire operator still couldn’t perform an inspection correctly. The inspection’s methods of the technicians and QC inspector are also needed to be changed because it still generates very high calculation variation. The result of Fishbone Diagram finds out that defective products are caused by these factors, such as machine, method, human, and material.